2019
DOI: 10.1111/1365-2664.13387
|View full text |Cite
|
Sign up to set email alerts
|

Pest control at a regional scale: Identifying key criteria using a spatially explicit, agent‐based model

Abstract: 1. Invasive mammals are a major threat to biodiversity. Understanding how their distributions and abundance could be affected by different temporal and spatial control strategies is fundamental for planning effective management programs.2. We developed a spatially explicit, agent-based model to test the impacts of different spatiotemporal management strategies on a pest population. As a case study, we used the common brushtail possum (Trichosurus vulpecula) population in the Cape-to-City treatment area in Hawk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Both individual and agent-based models simulate decision-making individuals; however, agent-based models consider individuals or "agents" to be adaptive and autonomous (Grimm et al, 2005). Therefore, individual-based models have been used to simulate nonautonomous invasive species (Tonini et al, 2014), while agent-based models can represent self-governing organisms (Lustig, James, Anderson, & Plank, 2019) or human behaviors involved in species spread or removal (Rebaudo & Dangles, 2013). Here, we refer to both individual and agent-based models as IBMs because they have similar mathematical foundations.…”
Section: Individual-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both individual and agent-based models simulate decision-making individuals; however, agent-based models consider individuals or "agents" to be adaptive and autonomous (Grimm et al, 2005). Therefore, individual-based models have been used to simulate nonautonomous invasive species (Tonini et al, 2014), while agent-based models can represent self-governing organisms (Lustig, James, Anderson, & Plank, 2019) or human behaviors involved in species spread or removal (Rebaudo & Dangles, 2013). Here, we refer to both individual and agent-based models as IBMs because they have similar mathematical foundations.…”
Section: Individual-based Modelsmentioning
confidence: 99%
“…The model integrated social learning of farmers and found that negative public opinions on invasive species control communicated by media outlets contributed to control program failure. Lustig et al (2019) built an IBM to test the success of management strategies for invasive brushtail possums (Trichosurus vulpecula) in New Zealand and incorporated sophisticated species-habitat interactions and spatially explicit carrying capacities. They showed that the optimal spatial control strategy depended on management effort.…”
Section: Individual-based Modelsmentioning
confidence: 99%
“…This research was conducted with the aim of gathering baseline data of urban possums in New Zealand in order to effectively plan and achieve future possum control and biodiversity outcomes. These data would also improve predictive possum models, which to date have made the unsupported assumption that possum density in urban areas is zero (Warburton et al 2009;Shepherd et al 2018;Lustig et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ABM has found applications in many study areas including biology, disease risk, social sciences, and economics (Polhill et al, 2008; Grimm & Railsback, 2013; Kilmek et al, 2015; Willem et al, 2017) with the unifying goal of investigating and predicting the dynamics of complex systems (Grimm et al, 2005). In particular, wildlife studies have adopted the ABM approach to simulate population growth, reproduction, mortality rate, energy budget, and migration ecology, just to cite a few (Brown & Robinson, 2006; Lustig et al, 2019; Aurbach et al, 2020; Goldstein et al, 2021). However, we currently lack a robust and spatially explicit ABM coding platform for the implementation of large-scale animal movement investigations (but see Thiele et al (2012) or Chubaty and McIntire (2021)).…”
Section: Introductionmentioning
confidence: 99%